Breeding value of candidate bulls based on birth weight in Kebumen Ongole Grade Cattle - Fathoni, Akhmad; Sumadi, Sumadi; Maharani, Dyah (2019)
orrelated with slaughter weight. The study aimed to estimate breeding value of candidate bulls in Kebumen Ongole Grade cattle based on birth weight. One thousands and five (1005) heads of offsprings generated from 127 sires and 868 dams were used in this study. Heritability was calculated using paternal half sib correlation method. Breeding Value (BV) was calculated based on absolute dan relative value. The results showed that the heritability (h) of birth weight was in high category (0.76 ± 0.12). Ten candidate bulls with the high breeding values (35.92 – 34.99) were obtained. These results are expected to be an initial recommendation in selecting candidate bulls in Kebumen based on BV.